Islamic Society and Family Planning Media Advertisements in Pakistan: Mediating Role of Religiosity in Attitude and Behavioral Intention - Abdul Rehman Madni; Malik Adnan; Ali Hassan (Pakistan Journal of Islamic Research)
Religious beliefs and religiosity have a significant impact on behavior. People want to adopt family planning methods to avoid unintended and unwanted pregnancies but they do not use family planning because they do not get support from their religion and people with high religiosity level follow their religion more strictly. Literature indicates that religion is one of the major reasons for overpopulation in Pakistan. The main objective of this study is to investigate the moderating role of religiosity between positive feelings, negative feelings, and attitude of Pakistani Muslims toward advertisements of family planning and intention to adopt family planning methods. Data were collected from the 525 Pakistanis using a cross-sectional study design. This research adopted snowball sampling for data collection. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to test the hypotheses. Results of this study show religiosity significantly moderate the relationship between positive feelings toward advertisements of family planning and intention to adopt family planning methods, while there is no significant moderating role of religiosity between negative feelings, attitude toward advertisements of family planning and intention to adopt family planning methods.